Vol.2 - "Padhy, Prafullah (ed.)" (Delhi, 2006)
This book in 4 vols deals with matters related to crime and criminal behaviour. It includes fields such as crime statistics, criminal psychology, forensic science, law enforcement and detective methods. It adhers to the natural science model and borrows heavily from philosophy, psychology and sociology.
Keywords: Crimes